Psychological Symptoms in Health Professionals in Spain After the First Wave of the COVID-19 Pandemic - Dosil, María; Ozamiz-Etxebarria, Naiara; Redondo, Iratxe; Picaza, Maitane; Jaureguizar, Joana (Frontiers in Psychology, 2020)
Following the declaration of the COVID-19 outbreak as a global pandemic in March 2020, a state of alarm was decreed in Spain. In this situation, healthcare workers experienced high levels of stress, anxiety and depression due to the heavy workload and working conditions. Although Spain experienced a progressive decline in the number of COVID-19 cases until the last week of May (when a flattening of the case curve was achieved) and the work overload among health workers was substantially reduced, several studies have shown that this work overload is associated with the later emergence of psychological symptoms induced by stress. The aim of the present study was to evaluate the levels of stress, anxiety, depression, post-traumatic stress and compassionate fatigue in health professionals. The sample consisted of 973 health professionals 16.5% men, 82.9% women and one non-binary person. The data were collected through an online questionnaire sent to the participants by e-mail. DASS-21 was used to measure anxiety, stress and depression, PCL-C to measure post-traumatic stress and ProQOL -vIV to measure compassion fatigue. In addition, other descriptive variables that could be related to these levels of psychological symptomatology were evaluated. The results reveal that after the work overload experienced during the COVID-19 pandemic, healthcare workers report psychological symptoms, post-traumatic stress and compassion fatigue. It is therefore recommended that these professionals be provided with psychological help in order to reduce the emotional impact of COVID-19, and consequently improve their mental health.